Constructions of urban space - Hutchinson, Ray (Research in urban sociology ;, 2000)
Urban space has emerged as the central organizing construct in studies of the post-modern metropolis. Contributors to this volume write on how urban space is used and contested by different social groups, how urban space is transformed by the changing economic relationships manifested in the new world order, and how urban space is defined by those who use and study it.